The Effect of Types and Doses Compost Fertilizer on Ylang-Ylang (Cananga odorata forma genuina) Seedling Growth - Irdika Mansur; Muhammad Ridwan Baihaqi (Jurnal Silvikultur Tropika, 2022)
The high economic value of ylang-ylang oil has encouraged some entrepreneurs to develop ylang-ylang plants in Indonesia, especially in terms of increasing productivity. The objectives of this research were to analyze the effect of two types of commercial compost and identify optimal dosage for the growth of ylang-ylang seedlings. The research was carried out through several stages, e.g. the procurement of seeds, weaning, maintenance, collecting and retrieving data, experimental design, hypothesis and data analysis. The research revealed that the use of two types of compost, with four doses used significantly affects the height parameter of the ylang-ylang seedlings. The use of doses of 25 g was able to increase the growth of ylang-ylang seeds better than other doses. Keywords: commercial, compost, ylang-ylang